If it's not what You are looking for type in the equation solver your own equation and let us solve it.
28=-k+1-2k-9
We move all terms to the left:
28-(-k+1-2k-9)=0
We add all the numbers together, and all the variables
-(-3k-8)+28=0
We get rid of parentheses
3k+8+28=0
We add all the numbers together, and all the variables
3k+36=0
We move all terms containing k to the left, all other terms to the right
3k=-36
k=-36/3
k=-12
| 2x-8=-2x-56 | | 2x(60)=55(12) | | 18x+50=146 | | 9(x+4)=72+32 | | 26(4r-1)=26 | | -20-(-24=x/12 | | 8x+10x=30+4x | | 3c+2=7c | | F(x)=1/5x+1 | | b-4+4b=24 | | -7n-21=-49 | | 7/c+4=35/55 | | -26-5d=-8(7d+9) | | 10(.7)^x+17=38 | | 2x´2–8x–10=32 | | 100+8d=400 | | 8+2x=66 | | 4x=19+3× | | 214×2=f | | (5b-5)(2b-3)=0 | | b^2+4b+8=0 | | x+720=2400 | | x+8x-(x+1)=5(x+2) | | H(t)=-16t+128t+50 | | x-720=2400 | | 9y^2-40y-16=0 | | -3(t+6)=9 | | (-2/5x)+3=(1/5x)+11 | | 24/13=b/26 | | N+44=45n | | 7b+6=99 | | 1x=13/10 |